Reconstructing the phylogeny of Blattodea: robust support for interfamilial relationships and major clades - Zongqing Wang (Nature Portfolio, 2017)
Abstract Cockroaches are among the most recognizable of all insects. In addition to their role as pests, they play a key ecological role as decomposers. Despite numerous studies of cockroach phylogeny in recent decades, relationships among most major lineages are yet to be resolved. Here we examine phylogenetic relationships among cockroaches based on five genes (mitochondrial 12S rRNA, 16S rRNA, COII; nuclear 28S rRNA and histone H3), and infer divergence times on the basis of 8 fossils. We included in our analyses sequences from 52 new species collected in China, representing 7 families. These were combined with data from a recent study that examined these same genes from 49 species, resulting in a significant increase in taxa analysed. Three major lineages, Corydioidea, Blaberoidea, and Blattoidea were recovered, the latter comprising Blattidae, Tryonicidae, Lamproblattidae, Anaplectidae, Cryptocercidae and Isoptera. The estimated age of the split between Mantodea and Blattodea ranged from 204.3 Ma to 289.1 Ma. Corydioidea was estimated to have diverged 209.7 Ma (180.5–244.3 Ma 95% confidence interval [CI]) from the remaining Blattodea. The clade Blattoidea diverged from their sister group, Blaberoidea, around 198.3 Ma (173.1–229.1 Ma). The addition of the extra taxa in this study has resulted in significantly higher levels of support for a number of previously recognized groupings.